2019
DOI: 10.3174/ajnr.a5952
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Dynamic Susceptibility Contrast Perfusion-Weighted MR Imaging and 11C-Methionine PET/CT for Differentiation of Tumor Recurrence from Radiation Injury in Patients with High-Grade Gliomas

Abstract: BACKGROUND AND PURPOSE: Both 11 C-methionine PET/CT and DSC-PWI could be used to differentiate radiation injury from recurrent brain tumors. Our aim was to assess the performance of MET PET/CT and DSC-PWI for differentiation of recurrence and radiation injury in patients with high-grade gliomas and to quantitatively analyze the diagnostic values of PET and PWI parameters. MATERIALS AND METHODS: Forty-two patients with high-grade gliomas were enrolled in this study. The final diagnosis was determined by histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 27 publications
3
51
0
1
Order By: Relevance
“…A direct comparison of MET versus FDG PET imaging obtained on the same day concluded that MET was more reliable in identifying recurrent tumor than FDG, and this has been confirmed by subsequent meta‐analysis . Combining MET‐PET and DCE perfusion imaging modalities similarly demonstrated significantly increased sensitivity and specificity for identifying TP . Nonetheless, the clinical use of MET is complicated by its short half‐life of 20 minutes, requiring an onsite cyclotron and precise coordination of its administration …”
Section: Introductionmentioning
confidence: 81%
“…A direct comparison of MET versus FDG PET imaging obtained on the same day concluded that MET was more reliable in identifying recurrent tumor than FDG, and this has been confirmed by subsequent meta‐analysis . Combining MET‐PET and DCE perfusion imaging modalities similarly demonstrated significantly increased sensitivity and specificity for identifying TP . Nonetheless, the clinical use of MET is complicated by its short half‐life of 20 minutes, requiring an onsite cyclotron and precise coordination of its administration …”
Section: Introductionmentioning
confidence: 81%
“…Другие пытаются разграничить подтипы глиом с выделением опухолей, содержащих олигодендроглиальный компонент [23,25]. В целом исследователи с большой осторожностью используют ИН как единственный маркер именно степени анаплазии, чаще всего сравнивая его чувствительность и специфичность с такими МРТ-методиками, как диффузионно-взвешенные изображения и Т2*-перфузия [26]. В то же время практически все авторы сходятся во мнении, что высокие значения ИН (более 2,0) и особенно увеличение индекса в ходе динамического наблюдения за пациентом достоверно коррелируют с малигнизацией глиальных новообразований.…”
Section: методы исследования и диагностики Methods Of Investigation Aunclassified
“…Moreover, in case of high-grade gliomas, 11 C-MET uptake is higher than in low-grade tumors therefore it could be used for monitoring purposes to assess anaplastic transformation [48]. In a recent study of 18 lesions from 15 patients with metastatic brain tumors who underwent gamma-knife radiosurgery, the authors showed that MET-PET was superior in terms of both sensitivity and specificity as imaging technique for differentiating RN and recurrent metastatic tumors after gamma-knife compared with diffusion weighted imaging (DWI), MR permeability imaging and FDG-PET, although it is not widely available yet for clinical use due to its physical limitations [49]. For the detection of tumor recurrence, compared to 201 Tl, 18 F-FDG is more specific but less sensitive since the former, prior to its uptake through the Na + -K + ATPase pump, has a non-specific accumulation due to BBB breakdown, whereas the latter lacks sensitivity because of the physiological uptake of normal brain [45].…”
Section: F-fdgmentioning
confidence: 99%
“…Moreover, in case of high-grade gliomas, 11 C-MET uptake is higher than in low-grade tumors therefore it could be used for monitoring purposes to assess anaplastic transformation [48]. In a recent study of 18 lesions from 15 patients with metastatic brain tumors who underwent gamma-knife radiosurgery, the authors showed that MET-PET was superior in terms of both sensitivity and specificity as imaging technique for differentiating RN and recurrent metastatic tumors after gamma-knife compared with diffusion weighted imaging (DWI), MR permeability imaging and FDG-PET, although it is not widely available yet for clinical use due to its physical limitations [49].…”
Section: C-metmentioning
confidence: 99%